Genetic variation and genetic structure of Caranx hippos (Teleostei: Carangidae) in the Colombian Caribbean - Caiafa Hernandez, Itala Ivonne (2018)
Studies based on molecular genetics offer the possibility to understand the structure of populations and provide data to implement measures designed to protect them. Caranx hippos, is a fish with a wide distribution in the Western Atlantic, becoming one of the most economically important species in the artisanal fishing industry in Colombia. However, little is known about its biology. The present study aimed to evaluate the variation and genetic structure of C. hippos in the Colombian Caribbean by analyzing the mitochondrial DNA region control and cytochrome oxidase subunit (COI). We sequenced the DNA of 153 muscle samples collected from specimens obtained from six fishing ports. The results showed 21 haplotypes for COI and 116 haplotypes for the control region, divided into two lineages that do not exhibit a pattern of geographical distribution. For mitochondrial control region, the estimated haplotype diversity (Hd) presented relatively high values (Hd = 0.99 and = 0.1), while for COI results were Hd = 0.68 and = 0.01; the relationship between haplotype and nucleotide diversity and the neutrality test revealed that C. hippos experienced bottlenecking and a subsequent rapid population expansion. Estimates of genetic structure were low and insignificant, indicating no differentiation between samples collected from geographical isolation. This suggests that for the Colombian Caribbean there is a panmictic population of C. hippos. However, variations were found at population levels, especially in La Guajira, Turbo and San Antero, which, when compared to those included for Brazil and México, demonstrated that unique haplotypes in La Guajira are more aligned to the Brazilian populations, by means of the influence of the Caribbean Current, whilst those from Turbo and San Antero are more frequent in haplotypes originating from Mexico. Future studies should focus the understanding of these processes.